Author's Acceptance in Relating Reader’s Response to Digital Novels - Trie Utari Dewi; Ade Hikmat; Prima Gusti Yanti; Sukardi Sukardi (Universitas Muhammadiyah Malang, 2025)
Technology development in the digital era has transformed the world of literature, particularly for digital novels. The comment sections on digital literature provide a platform for direct interaction between authors and readers, which can influence the author's creative process. Therefore, this research aims to examine the author acceptance in responding to readers' feedback on their digital novels and to explore its impact on the creative process of the works produced. This study employed a descriptive qualitative method with a literary reception approach to understand readers' responses to three digital novels: